VD_FINDINFO Décision / 2012 / 240 vom 5. Oktober 2011 - VD Tribunal cantonal (2011)
PROPORTIONNALITÉ, DÉTENTION PRÉVENTIVE, SURSIS À L'EXÉCUTION DE LA PEINE | 212 al. 3 CPP (CH), 221 CPP (CH), 227 CPP (CH), 229 CPP (CH)